LOKASI DAN HARGA BERPENGARUH TERHADAP KEPUTUSAN PEDAGANG MENYEWA KIOS (Studi Kasus Pada Pasar Kemiri Muka Kota Depok) - Raymundus I Wayan Ray (The Indonesian Journal of Public Administration (IJPA), 2018)
Abstract: The purpose of this study was to determine how much influence the location and price in making decisions to rent kiosks. The method used in this study is a method of quantitative analysis and the population is traders as many as 922 people and the sample taken is 90 people. The hypothesis in this study is that there is a positive and significant influence between the independent variable and the dependent variable.          The results showed that the tcount was 2.220 with a significance of 5%. The value of table for the amount of data is 90 and the independent variable is 2 with a significant level of 5%, then the value of t table is 1.987. Then we compare, if thitung> from t table then the variable is stated significant. Because tcount for variable X1 (2,220) is greater than t table (1,987) then the decision Ha is accepted, meaning that the location variable has a positive and significant influence on the decision to rent a kiosk.        The price variable also shows the tcount value of 2.351 with a significance of 5%. The value of t table for the amount of data is 90 and the independent variable is 2 with a significant level of 5%, then the value of t table is 1.987. Then we compare, if thitung> from t table then the variable is stated significant. Because tcount for variable X2 (2,351) is greater than t table (1,987), then the decision Ha is accepted, meaning that the price variable has a positive and significant influence on the decision to rent a kiosk.         Thus it can be concluded that the price factor has a greater percentage among the variables that are equal to 23% but the location factor also has a percentage of 22% so that between location and price has a positive and significant influence in the consideration of traders to rent kiosks in the Market Kemiri Muka City Depok.Keywords: Location, price and decision to rent a kiosk